Manly Militants, Cohesive Communities, and Defiant Domestics: Writing about Immigrants in Canadian Historical Scholarship - Iacovetta, Franca (Labour / Le Travail, 1995)
A chapter of the book "Labour/Le Travail" is presented. It explores the historical works on immigrants in Canada that offer significant contributions to immigrant history in the country. It highlights the emergence of new approaches that promote new ways of writing about immigrants. It highlights the belief of scholars that race-ethnicity is a significant category of analysis as well as issues on the popularity of the class-gender-race/ethnicity analytical framework.
Keywords: Canada; Ethnicity; IMMIGRANTS – History; LABOUR/LE Travail (Book); SCHOLARS